Polymer Composition

JP7668792B2Active Publication Date: 2025-04-25OXFORD MEDICAL PROD LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022521632
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-11
Filing Date
2020-10-12
Publication Date
2025-04-25
Estimated Expiration
2040-10-12

AI Technical Summary

Technical Problem

Existing methods for producing superporous hydrogels require high compressive forces, multiple steps, and are inefficient in controlling pore size, leading to compromised quality and difficulty in manipulating the hydrogels for oral dosage formulations.

Method used

A method involving the use of freeze-drying and controlled acid and monovalent metal salt treatments to produce superporous hydrogels that can be directly molded or compressed into oral dosage capsules, eliminating the need for sheet formation and multiple steps, while ensuring rapid swelling and controlled pore size.

Benefits of technology

The method enables easy manipulation and rapid swelling of superporous hydrogels, allowing them to be directly molded into oral dosage forms with enhanced swelling volumes and rates, suitable for gastric retention and controlled release of pharmaceuticals or nutraceuticals, and can be terminated naturally or chemically.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000025_0000
    Figure 00000025_0000
  • Figure 00000026_0000
    Figure 00000026_0000
  • Figure 00000026_0001
    Figure 00000026_0001
Patent Text Reader

Abstract

The present invention provides a method for preparing a plasticized superporous hydrogel material, which comprises treating an initial hydrogel material with an acidic solution, an optional monovalent metal salt solution, freeze-drying, and plasticizing. Optionally, the method produces a shaped plasticized superporous hydrogel body having one or more through-holes formed therein. The plasticized superporous hydrogel material of the present invention can be formulated into a suitable oral dosage form for use as an appetite suppressant and for use in delivering pharmaceuticals and / or dietary supplements to the human or animal body.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for preparing a hydrogel material that can be manipulated more easily and reliably and has an increased swelling volume and an increased swelling rate compared to known hydrogel materials. The hydrogel material produced by the method of the present invention is particularly suitable for use as or in oral dosage capsules, for example, as an appetite suppressant for both humans and animals. Furthermore, the hydrogel material produced by the method of the present invention, both when used per se (as produced) and when used in the form of an appropriate dosage formulation, can contain, incorporate, or encapsulate one or more pharmaceuticals, dietary supplements, or foreign substances that are dissolved or otherwise delivered within the human or animal body, or generally in any liquid (preferably aqueous) medium-based application. [Background technology]

[0002] As described in "Recent Developments in Superporous Hydrogels" by H. Omidian et al., J. Pharm. & Pharmacol. 2007, 59:317-327, superporous hydrogels (SPHs) are porous, hydrophilic, crosslinked structures that become rigid and brittle when dry and are insoluble in water. However, when immersed in an aqueous medium, they can absorb aqueous fluids up to many times their own weight, expanding in size and becoming soft, flexible gel materials. SPHs typically have a three-dimensional network made of hydrophilic polymeric materials, with numerous pores with average sizes greater than 100 μm and up to about 1 or 2 mm. These pores connect to each other to form an open-channel structure, allowing them to absorb water very rapidly using capillary action. Maximum swelling is generally achieved in a fraction of a second, and SPHs swell to their equilibrium size.

[0003] Recently published patent application WO2019016560(A1) describes a method for softening (plasticizing or malleable) dried superporous hydrogel material without the need for swelling. The method further describes applying a compressive force to flatten / collapse the hydrogel pores without destroying the bonds that hold the three-dimensional network together, thereby forming a sheet of plasticized superporous hydrogel material. Oral dosage formulations can be produced by cutting samples from a sheet of superporous hydrogel material, folding / rolling these samples, and then inserting them into oral dosage capsules. Such oral dosage formulations dissolve or rupture upon contact with aqueous media (e.g., gastric fluids when the capsule is swallowed by a human or animal), and the superporous hydrogel contained within then rapidly swells to many times its original size. These formulations are disclosed to make excellent appetite suppressants and useful alternatives to gastric balloons in the treatment of obesity. Summary of the Invention

[0004] The present invention seeks to provide a rapid, cost-effective, and reliable method for producing superporous hydrogel materials that have excellent physical properties (including swelling volume, swelling rate, and overall strength) and, importantly, can be easily manipulated to facilitate, for example, direct molding or insertion into the casing of an oral dosage formulation. The objective of the present method is to avoid the need to form sheets of plasticized superporous hydrogel (e.g., by applying high compressive forces to as-made plasticized superporous hydrogel materials) and to avoid the need to cut hydrogel samples from the sheets and then roll them prior to insertion into oral dosage capsule casings. Ideally, therefore, the superporous hydrogels produced by the present method can be poured into molds and then manipulated directly into, for example, oral dosage capsule casings (shells). Alternatively, the superporous hydrogels produced by the present method can be directly molded or compressed into lozenge-shaped dosage forms for direct oral administration.

[0005] The present invention further provides an ultraporous hydrogel material that, upon swallowing and swelling, possesses mechanical robustness that allows products made therefrom to be retained in the human or animal stomach for a limited period of time, e.g., 1-4 weeks, without degradation or digestion. Therefore, it can be used in appetite suppression and appetite control applications in overweight / obese animal or human patients, or as a delivery vehicle for the controlled release of pharmaceuticals or nutritional supplements within the animal or human body. Over time, e.g., 1-4 weeks later, it begins to naturally degrade or disintegrate and is naturally excreted from the body. A suitable appetite suppressant is ideally a tablet or other suitable oral dosage form designed to be taken at home, without the need for a hospital or medical setting. Ideally, the appetite suppressant of the present invention does not require surgery, endoscopy, or radiation to insert, adapt, or accurately check the placement of the appetite suppressant formulation within the patient's body. Advantageously, such appetite suppressant formulations are effective for days or weeks at a time before termination is triggered by spontaneous degradation or by the consumption of approved chemical or natural food sources, followed by excretion. More advantageously, the present invention provides an appetite suppressant that allows patients to ingest larger or smaller doses of one or more superporous hydrogels and terminate the effect of the ingested appetite suppressant product at will. Therefore, the present invention also provides a method for dissolving the appetite suppressant formulation of the present invention ingested by a patient, thereby providing an appetite suppressant product customized according to the required intensity and duration of the weight management process.

[0006] In a further aspect, the present invention provides a plasticized superporous hydrogel material for use in oral dosage formulations (e.g., dosage capsules) that may further contain one or more pharmaceuticals and / or nutritional supplements designed to be eluted or delivered into the human or animal body when the capsule is in a specific location within the body (e.g., the stomach or intestine). Ideally, the pharmaceuticals / nutraceuticals are eluted / delivered over an extended period of time. In one embodiment, it is envisioned that one or more pharmaceuticals and / or nutritional supplements are incorporated into the oral dosage formulation as separate components in addition to the plasticized hydrogel material. In this embodiment, the pharmaceuticals and / or nutritional supplements may be used alone or in combination with one or more additives. Alternatively, the pharmaceuticals and / or nutritional supplements may be associated with or contained within a separate drug delivery device, such as a liposome. In another further embodiment, the pharmaceuticals and / or nutritional supplements may be part of the structure of the hydrogel material; for example, the pharmaceuticals and / or nutritional supplements may be attached to the hydrophilic polymer chains that form the hydrogel material. As used herein, the term "dietary supplement" should be construed to include any dietary supplement, mineral or vitamin that confers a health-promoting benefit when taken by a human or animal.

[0007] In a preferred embodiment, the present invention provides a method for preparing a plasticized superporous hydrogel material comprising the steps of: a) forming an initial hydrogel material without the use of a foaming agent or other foaming means, said initial hydrogel material comprising one or more selected from an interpenetrating network, a semi-interpenetrating network, and a simply crosslinked network formed by providing a mixture comprising one or more hydrophilic polymers and / or copolymers and subjecting said mixture to polymerization and / or crosslinking conditions; b) recovering the resulting initial hydrogel material formed in step a) and treating it with an acidic solution comprising one or more acids and having a pH in the range of <1 to ≦3; c) simultaneously with or subsequent to treating step b), treating the initial hydrogel material formed in step a) with a ≧0M to ≦0.5M solution comprising one or more monovalent metal salts; d) drying the resulting wet initial hydrogel material using freeze-drying to produce a dry superporous hydrogel material; e) treating the resulting dried superporous hydrogel material to plasticize its structure; f) recovering the resulting plasticized superporous hydrogel material.

[0008] It is known in the prior art to use a blowing agent or other foaming means during the polymerization / copolymerization and crosslinking process. While this produces a "superporous" hydrogel, the present inventors have found that the efficiency of the process and the quality of the final superporous hydrogel are compromised. First, the use of a blowing agent or other foaming means during the polymerization step requires the superporous hydrogel product material to be separated from the polymer reaction mixture and then dried. The usual method for achieving drying is air drying or oven drying, but as explained below, the present inventors have found that such processes are too slow to ensure that all of the solvent (typically water) is removed quickly enough to prevent pore collapse. Second, pore size is determined by the size of the gas bubbles generated by the blowing agent or provided by the foaming means, and the size of these bubbles is difficult to manage, resulting in difficulty in controlling pore size. Third, the use of a blowing agent or other foaming means and the subsequent separation / drying of the resulting superporous hydrogel constitute two steps, whereas the present invention requires only a single freeze-drying step to achieve both superporosity and drying. Finally, fourth, the use of blowing agents, typically sodium carbonate or sodium bicarbonate as the pore-forming gas, as opposed to the common carbon dioxide, requires that the polymerization step be carried out under acidic conditions, which may be advantageous for systems producing acrylic acid-based polymers, but not when using acrylamide- or amide-based polymers.

[0009] The ideal initial hydrogel for use in the methods of the present invention is a "co-hydrogel," i.e., a hydrogel comprising two or more cross-linked interpenetrating scaffolds formed from one or more hydrophilic polymers and / or copolymers. The swelling rate and subsequent degradation rate of the resulting plasticized superporous hydrogel material are advantageously much easier to control when the hydrogel comprises two or more cross-linked interpenetrating scaffolds compared to hydrogels made with a single cross-linked scaffold.

[0010] The hydrophilic polymers and / or copolymers may be derived from naturally occurring polymers and monomers, from synthetic polymers and monomers, or from a mixture of naturally occurring and synthetic polymers and monomers. Preferably, the one or more hydrophilic polymers are hydroxylated polymers, and more preferably, the hydrophilic polymers are selected from C1-C6-alkyl celluloses, hydroxy C1-C6 alkyl celluloses, hydroxy C1-C6 alkyl C1-C6 alkyl celluloses. More preferably, the one or more hydrophilic polymers are selected from methylcellulose, ethylcellulose, n-propylcellulose, hydroxyethylcellulose, hydroxy-n-propylcellulose, hydroxy-n-butylcellulose, hydroxypropylmethylcellulose, ethylhydroxyethylcellulose, carboxymethylcellulose, carboxymethyl starch, chitosan, alginate, cationic dextrans (e.g., dextran sulfate, dextran phosphate, dimethylaminodextran, diethylaminodextran, cationic dextrins, polyetherimides, heparin, hyaluronic acid, chondroitin, sulfate, methylcellulose ... The hydrophilic polymer(s) may be selected from chondroitin, heparan sulfate, polygalacturonic acid, polyanuronic acid, polygalacturonic acid, polyarabinonic acid, and polylysine. In some cases, the hydrophilic polymer(s) may be prepared by polymerization and / or copolymerization of one or more monomers selected from C1-C6 alkenyl amides (e.g., to prepare polyacrylamide) and C1-C6 alkenyl acids (e.g., to prepare acrylic acid). Other possible preferred polymers include poly(acrylamide), poly(2-acrylamido-2-methyl-1-propanesulfonic acid), and poly(N-isoacrylamide).

[0011] It is particularly advantageous that the one or more hydrophilic polymers and / or copolymers used in the method of the present invention are derived at least in part from amine monomers and / or acrylamide monomers and / or amine moiety-containing monomers and / or acrylamide moiety-containing monomers, optionally with polymers containing multiple OH groups and / or multiple OH group-containing monomers. Suitable multi-OH group-containing materials include alginates, chitosan, and other sugar- or carbohydrate-containing materials. Advantageously, the crosslinker contains calcium. It is preferred that the one or more hydrophilic polymers are not derived from acrylic acid monomers or acrylic acid moiety-containing monomers.

[0012] The initial hydrogel is preferably prepared using one or more hydrophilic polymers and / or one or more monomers as described above, optionally in combination with one or more additional components selected from biocompatible polymers and mechanically strong hydrogels.

[0013] Suitable biocompatible polymers include one or more selected from polyallyl alcohol, polyvinyl alcohol, polyacrylic acid, polyethylene glycol, and poly(N-vinyl-2-pyrrolidone) (PVP), which may be copolymerized with one or more additional polymers (e.g., acrolein).

[0014] Ideally, the one or more hydrophilic polymers (as described above) from which the initial hydrogel is made are selected to impart appropriate mechanical properties or toughness to the final product, or a suitable mechanically strong hydrogel can be added either to the initial hydrogel once formed or to the mixture of one or more monomers used to prepare the initial hydrogel. Such strong materials include non-superporous, slowly swelling hydrogels (also known as superabsorbent polymers (SAPs)), which are hydrophilic networks capable of absorbing and retaining large amounts of water or aqueous solutions. Preferably, they can uptake as much as 100,000% water. More preferably, the one or more mechanically strong, slowly swelling non-superporous hydrogels are selected from double network hydrogels (DN), nanocomposite hydrogels (NC), topological hydrogels (TP), and polymer composite hydrogels (MMC). Particularly useful slow-swelling non-superporous hydrogels include, but are not limited to, poly(2-acrylamide, 2-methyl, 1-propanesulfonic acid) (PAMPS)-polyacrylamide (PAAm) double-network hydrogels, algarose-hydroxyethyl methacrylate (HEMA) double-network hydrogels, alginate-PAAm double-network hydrogels, poly(N-isopropylacrylamide) and poly(N-isopropylacrylamide)-Laponite nanocomposite hydrogels. Although such slowly swelling non-superporous hydrogels have limited swelling rates, they can nevertheless possess reasonable swelling capacities of up to 15-20 times the volume increase from xerogel to fully swollen state. Once they reach their swelling equilibrium, non-superporous hydrogels can still retain maximum engineering compressive strengths of 2-3 MPa or more, but generally have limited volumetric swelling ratios. Suitable non-superporous hydrogels may exhibit high overall swelling capacity, but may exhibit slower swelling rates than the high volume swelling superporous hydrogels of the present invention.

[0015] Samples of the initial hydrogel material are preferably made by a casting process, which may involve filling a mold of appropriate shape and size with a mixture of polymers and / or monomers (along with one or more optional additional components, as described above) and subjecting the mixture to the addition of one or more crosslinking agents, irradiation (e.g., high-energy ionizing radiation (e.g., electron beam (e-beam), gamma rays, or X-ray irradiation)), and / or other conditions suitable for producing a crosslinked, polymerized, and / or copolymerized interpenetrating network of the hydrogel, or a semi-interpenetrating network or simply crosslinked structure (e.g., sulfur vulcanization or other suitable chemicals, optionally in combination with heat and / or increased pressure). However, it is important to control the degree of crosslinking so as not to interfere with the swelling volume ratio of the product. Ideally, the demolded initial porous hydrogel is in individual pieces, with typical dimensions ranging from 15 mm x 25 mm to 40 mm x 60 mm. The individual pieces (samples or bodies) of the initial porous hydrogel can be of any suitable shape and / or size, and are preferably cubes, cuboids, ovals, pellets, beads, balls, cylinders, rods, or irregular shapes. In an alternative process, the initial hydrogel material is molded or extruded, for example, into long cylinders or tubes of a predesigned diameter, and then cut to the required length after curing (crosslinking).

[0016] The initial hydrogel material of an individually molded or cut and extruded sample preferably has an inner body portion (which may be solid or hollow) and an outer surface that is the outer boundary of the inner body portion formed against the inside of a mold or extrusion die.

[0017] Alternatively, the initial hydrogel material sample may be unshaped, but preferably has an inner body portion having an internal structure comprising the plasticized superporous hydrogel material, and an outer surface that is the outer boundary of the inner body portion.

[0018] The processing steps described below are equally applicable to unshaped and shaped (including cast and non-cast) initial hydrogel materials (e.g., as-made, or in sheet form, or extruded, or otherwise compressed).

[0019] Once prepared, the initial hydrogel material is preferably washed with a suitable solvent (ideally distilled water) to remove any unreacted hydrophilic polymer and / or monomer from the initial hydrogel. The initial hydrogel material is then treated with at least one acidic material (preferably by immersion in an acidic solution) for up to 14 days, preferably 7-14 days, and further preferably flushed with water (ideally distilled water) and retreated with fresh acidic material or preferably reimmersed in fresh acidic solution. Typically, the volume of acidic solution used to immerse the initial hydrogel sample is 15-50 ml per initial hydrogel sample, which will swell the sample of initial hydrogel material. As described below in the specific examples, acid treatment beneficially i) improves the swelling rate of the target plasticized superporous hydrogel material, ii) allows for control of the percent change in swelling volume, iii) allows for control of the degree of porosity in the target superporous hydrogel, and iv) allows for control over the malleability (also referred to herein as "ease of processing" or "workability") of the target superporous hydrogel.

[0020] However, it is important to note that the acid treatment step involves treating the isolated initial hydrogel material formed in step a) with at least one acidic material at a pH in the range of <1 to ≦3, more preferably <1 to <3, very preferably 1 to <3, and most preferably 1 to 2.8. Applicants have found that using a pH in the range of <1 to ≦3 is advantageous in order to protonate the hydrogel and thereby achieve larger pore sizes during the freeze-drying step. Furthermore, the inventors have observed that the final plasticized superporous hydrogel obtained by the present invention achieves the required rate and degree of swelling at low pH (e.g., in the stomach) and disintegrates (if necessary) at high pH (e.g., in the duodenum).

[0021] Treatment of the initial hydrogel material with an acidic solution with a pH greater than 3 has been found to cause the structural integrity of the target plasticized superporous hydrogel material to be lost. That is, the target superporous hydrogel (SPH) material body created from the initial hydrogel treated with an acidic solution at pH > 3 loses its defined shape (this is particularly evident in the case of cast hydrogel materials). Furthermore, the porosity of the target superporous hydrogel also decreases, slowing its swelling rate. Specifically, the SPH body becomes increasingly distorted and less porous as the pH increases from > 3 to pH 9, becomes highly distorted at pH 10 and pH 11, and becomes a gelatinous mass or highly viscous fluid at pH 12 or above. Ideally, the acid solution used to treat the initial hydrogel comprises an aqueous solution of one or more acidic materials. The one or more acidic materials may be inorganic and / or organic acids. Stronger acids have been found to be more beneficial than weaker acids, with materials having a pKa in the range of -15 to 3.5 being preferred. A pKa in the range of -15 to 3.0 is particularly preferred, a pKa in the range of -15 to 2.5 is even more preferred, and a pKa in the range of -15 to 1 is extremely preferred. Suitable inorganic acids include hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid. Suitable organic acids include citric acid, oxalic acid, tartaric acid, maleic acid, malic acid, and toluenesulfonic acid. A 1 to 100 mM acidic aqueous solution is preferred, and a 80 to 90 mM acidic aqueous solution is even more preferred.

[0022] The one or more acidic substances may be derived from substances obtained or extracted from the animal or human body, or made from compositions that mimic such substances, with acidic solutions comprising gastric juice and / or artificial gastric juice being particularly preferred. The artificial gastric juice is preferably prepared without pepsin, and preferably contains 0.2% / wt sodium chloride and 0.7% / wt hydrochloric acid per liter of water, with a pH of about 1.2.

[0023] Concurrently with, or alternatively following, the treatment of the initial hydrogel material with at least one acidic material as described above, the initial hydrogel material is optionally further treated with a solution containing one or more monovalent metal salts, preferably selected from salts of sodium, potassium, and lithium. The inventors have found that such metal salt treatment allows for control of the plasticization process, which in turn determines the processability of the target material and ultimately affects production costs.

[0024] Any water-soluble monovalent metal salt can be used, including chlorides, bromides, iodides, nitrates, sulfates, and carbonates. Sodium chloride and potassium chloride are particularly suitable. The presence of a monovalent metal salt solution has been found to influence and advantageously control the processability (i.e., workability and manipulability) of the final plasticized superporous hydrogel. In particular, further processing and manipulability improvements in the final superporous hydrogel have been found to be proportional to the monovalent metal salt concentration up to 0.5M; at concentrations above 0.5M, the final plasticized superporous hydrogel becomes too soft to be easily processed within a reasonable time frame (desirably less than 1 minute to 60 minutes). Ideally, the monovalent metal salt solution is >0M to ≦0.5M, preferably >0M to ≦0.25M, and more preferably >0M to ≦0.14M.

[0025] In a particularly advantageous method of the present invention, the initial hydrogel material is treated with an acidic solution having a pH in the range of 1-2 in addition to a <0.2M solution (preferably a 0.13M solution) of an alkali metal salt (particularly a chloride), followed by freeze-drying to remove the solvent from the structure and produce a dry superporous hydrogel material.

[0026] The initial hydrogel naturally contains pores defined by the network / crosslink structure, but these pores are filled with the solvent (e.g., water) used in the polymerization reaction to form the initial hydrogel material. Generally, the more dilute the monomer / polymer mixture from which the initial hydrogel is made, the larger the pore size. Typically, the initial hydrogel has a density of about 1.30 g / cm. 3 It has a density of

[0027] It is important that the resulting treated initial hydrogel not be dried, for example, above room temperature, as this would cause the treatment solution to evaporate too slowly from the swollen pores of the treated initial hydrogel material, resulting in the water in the structure collapsing the pores, resulting in the loss of the desired pores and a significant reduction in the swelling rate.

[0028] However, the target material is a plasticized "superporous" hydrogel material, and therefore typically has a pore volume of 70-90% and a density of about 0.7-0.8 g / cm. 3 The initial hydrogel has a typical concentration of 100 μm to 1000 μm, ideally 200 μm to 500 μm, and therefore the pores initially formed in the initial hydrogel structure (typically having an average size of 100 μm to 1000 μm, ideally 200 μm to 500 μm in the largest dimension) must be enlarged / exposed to 5 mm. When enlarging the pore size, it is important to create the required enlarged pore size and then "fix" this size as quickly and efficiently as possible. Therefore, the initial hydrogel is subjected to a freeze-drying process either immediately after treatment with an acidic solution as described above, or immediately after treatment with a solution containing one or more monovalent metal salts, if used. Advantageously, freeze-drying is a fast and efficient drying process that quickly removes water, especially water retained within the pores as described above, before the pores have time to collapse.

[0029] The freeze-drying process is preferably carried out by first initially freezing the initial hydrogel treated with the acid (and any monovalent metal) solution in a conventional freezer or using an ultra-low temperature freezer (-20°C to -86°C), which causes the liquid (preferably water) within the pores to crystallize and expand (e.g., through hydrogen bonding interactions). The lower the freezing temperature used in the initial freezing process, the smaller the crystals and the smaller the final pore size. The acid-treated hydrogel sample is preferably placed in a mold 1.5 to 2.5 times larger in diameter than the initial acid / metal salt pre-treated hydrogel sample before undergoing the initial freezing process. The frozen sample is then freeze-dried using a freeze-drying apparatus (at -50°C to -80°C) until all of the inter-pore solution is removed, resulting in a superporous hydrogel material with the desired pore size (0.1 mm to 5 mm, preferably 0.5 mm to 1.0 mm). It is highly preferred that the superporous hydrogel material produced by the method of the present invention preferably contains the same number of pores per unit weight as the initial hydrogel from which it is produced.

[0030] An optional further step in the method of the present invention includes forming one or more through-holes, preferably 1 mm to 15 mm in diameter, more preferably 3 to 6 mm in diameter, and most preferably about 4 mm in diameter (before the plasticization step described below). The ratio of the diameter of the through-hole to the diameter of the superporous hydrogel material sample is preferably 0.75:1 to 1:30, more preferably 0.5:1 to 1:10, and most preferably 0.3:1 to 1:10. Ideally, each of the one or more through-holes comprises a channel or conduit within the body of the superporous hydrogel sample, extending from a first opening in a first portion of the outer surface of the superporous hydrogel sample to a second opening formed in a (preferably opposing) second portion of the outer surface of the superporous hydrogel sample. Preferably, the one or more through-holes are linear. For the avoidance of doubt, such "through-pores" are not formed directly as a result of the chemical polymerization / crosslinking reaction that forms the initial hydrogel, i.e., the "through-pores" are not pores formed between the crosslinked interpenetrating backbone of the initial hydrogel material; instead, such "through-pores" are formed as a result of a physical processing step.

[0031] When the superporous hydrogel sample is a cylindrical body, one or more through-holes are preferably formed so as to be aligned substantially parallel to the longitudinal axis of the sample. Non-cylindrical samples of superporous hydrogels preferably include one or more through-holes, which are aligned substantially perpendicular to the direction in which compressive forces will be applied to the final plasticized superporous hydrogel during further processing steps, such as for manipulating the plasticized superporous hydrogel into a dosage capsule, as discussed below. The through-holes may be formed using any suitable technique; for example, the mold used to form the initial hydrogel sample may be embedded in or molded to include one or more elongated members (e.g., elongated cylindrical members, pins, or needles) aligned parallel to the central axis of the mounds. Alternatively, the shape of the mold may be such that appropriate through-holes can be molded into the sample body as the initial hydrogel material body is formed. Alternatively, one or more through-holes may be drilled into the superporous hydrogel sample, for example, using a 3-15 mm drill, preferably at room temperature. Still further alternatively, each of the one or more through-holes may be formed by extruding an initial hydrogel over a mandrel.

[0032] The effect of one or more through-holes is to allow the final plasticized superporous hydrogel sample to be more easily compressed and folded upon application of a compressive force, as described above. Furthermore, the presence of through-holes also increases the surface area of ​​the final plasticized superporous hydrogel sample, which promotes faster swelling (expansion) of the sample compared to a similar sample without one or more through-holes. Furthermore, it has been found that final plasticized superporous hydrogel samples with through-holes can achieve a larger final swelling volume than similar samples without through-holes (assuming each has an equivalent dry volume), which is important when the final plasticized superporous hydrogel material produced by the method of the present invention is used in a gastroretentive system.

[0033] The toughness of the final plasticized superporous hydrogel material is a particularly important property that affects i) its ability to achieve a substantially unbroken / undamaged / intact structure after compression (discussed below), and ii) its ability to ensure that applied compressive forces can effectively compress the sample; more highly plasticized superporous hydrogels are more malleable and can withstand manipulations such as rolling / folding without cracking. Dried superporous hydrogel materials obtained by freeze-drying acid-treated initial hydrogel materials typically have a stiff, brittle structure that needs to be modified to increase their plasticity, allowing insertion of the hydrogel material into a 000-size dosage capsule, if desired. While the use of plasticizers (e.g., esters such as sebacate, adipate, terephthalate, dibenzoate, glutarate, phthalate, azelaate, and blends thereof) may be one solution to this problem (either by adding such agents to the reaction mixture in which the initial hydrogel is formed or by adding such agents to the initial hydrogel as it is formed), this is generally undesirable, particularly, but not exclusively, when the improved compressed hydrogel final product is used as a gastrointestinal appetite suppressant, where the use of a minimal number of chemicals reduces the risk of undesirable side effects. Therefore, highly preferably, an alternative means is used to reduce the glass transition temperature of the superporous hydrogel, thereby increasing its plasticity, prior to the application of compressive forces. A preferred alternative involves subjecting the freeze-dried superporous hydrogel to high humidity conditions (typically >55% to ≦100% humidity, preferably in the range of 65% to ≦100%), for example using water vapor (i.e., a humid environment), at room temperature or, preferably, at elevated temperatures. The use of steam is beneficial.The length of time the freeze-dried superporous hydrogel is exposed to high humidity (water vapor and as described above) is critical to the performance of the resulting final plasticized superporous hydrogel material. This duration depends on the original polymer composition of the initial hydrogel material (specifically, crosslink density, water content, and amount of initiator), the size and shape of the dried superporous hydrogel sample / body, the molarity of the monovalent salt solution, and the processing method used (including the freezing temperature and how the sample is frozen, i.e., whether it is frozen in an open or closed mold, the material of the mold, etc.). The water vapor processing step is preferably carried out in a lidded container containing a small amount of water, heated to 50-65 °C (preferably 60 °C) to generate the required % humidity level inside (as described above). Contact of the superporous hydrogel sample with water droplets (or visible water vapor) during plasticization can irreversibly deform the sample, primarily due to the collapse of the porous structure, which prevents the final product from fully expanding. Therefore, it is important to prevent condensation of water vapor, for example, on the walls of the container or the inner surface of the lid. Therefore, the surface of the inner wall of the lidded container preferably includes a coating of a wet, absorbent material, which not only helps to provide a uniform level of humidity within the container but also reduces the risk of condensed water dripping and falling / moving on the superporous hydrogel sample. The superporous hydrogel sample is placed in the container and sealed with a lid. The sample is then held in the container for the desired period of time, then immediately removed from the container and subjected to mechanical treatment / manipulation as described below. Treating the superporous hydrogel with steam for too long can result in irreversible deformation (mainly shrinkage), while insufficient treatment can result in insufficient plasticization of the superporous hydrogel sample. In the former case, the hydrogel is unlikely to be successfully compressed because it may become elastic and spring back to its original shape when the compressive force is released. In the latter case, further mechanical treatment may destroy the sample's structure. One useful advantage of treating the initial hydrogel with an acidic solution is the reduced time required for steam treatment.For example, at 60°C, typical steam treatment times for initial hydrogels treated with acid at pH 1-3 are 5-20 minutes (preferably 5-12 minutes), whereas otherwise identical samples of initial hydrogels not treated with an acid solution require steam treatment for more than 20 to 60 minutes or even longer to achieve a comparable degree of plasticization. Treatment of the initial hydrogel material with a monovalent metal salt solution, either simultaneously with or after treatment with an acid solution, allows for further control over the duration of steam treatment. Applicant has found that monovalent metal salt and acid-treated materials only require treatment under high humidity conditions (water vapor) at 60°C for 1-5 minutes, and highly preferably 3 minutes.

[0034] Another useful benefit of treating the initial hydrogel sample with an acid solution is that the initial hydrogel material treated with the acid solution has larger and better-connected pores than samples that have not been acid-treated; these larger and better-connected pores are more permeable and result in more efficient water absorption; i.e., such materials exhibit faster swelling and higher swelling volumes, as demonstrated in the specific examples below. Furthermore, during the acid treatment step, the gel is caused to swell slightly in all directions, and as a result of this swelling, more water can penetrate the polymer network, expanding the pores of the material. When this slightly swollen (expanded / water-loaded) material is frozen and then freeze-dried, the pores remain at their expanded size.

[0035] Once the superporous hydrogel is sufficiently plasticized, the sample is handled under appropriate humidity and temperature conditions to prevent hardening. The method of the present invention then preferably involves applying a compressive force having at least a radial component. In some cases, it may be desirable to form a thin sheet of plasticized superporous hydrogel by reducing the initial thickness of the plasticized superporous hydrogel by 50% or less, preferably 30% or less, and most preferably 15% or less (i.e., the initial hydrogel thickness is reduced by at least 50%, preferably at least 70%, and most preferably at least 85% after compression).

[0036] The application of compressive force collapses / flattens the pores in the plasticized superporous hydrogel and is accomplished using any suitable means or device, for example, by applying a compressive force between one or more pairs of rollers, and / or by applying pressure using one or more plates, and / or by using a vacuum to assist in providing at least a partially radial compressive force. As described in WO2019016560(A1), once the plasticized superporous hydrogel sheet is formed, it may be rolled, folded, pleated, corrugated, wound, corrugated, cut, extruded, or shaped prior to insertion into an oral dosage capsule.

[0037] In the case of shaped plasticized superporous hydrogel materials, Applicants have found it beneficial to manipulate (e.g., fold and / or crush) the shaped plasticized superporous hydrogel material as formed (i.e., directly without first forming a sheet), for example, inserting it into an oral dosage capsule. As discussed above, the initial hydrogel material can be shaped into any desired shape. If the initial hydrogel, and thus the plasticized superporous hydrogel, is a cylindrical sample, it may be desirable to form one or more through-holes or channels within the body of the superporous hydrogel, as discussed above. A compressive force can then be applied to the plasticized superporous hydrogel, preferably either radially or in a combination of radial and axial directions relative to the longitudinal axis of the shaped plasticized superporous hydrogel material. In a preferred example, a compressive force can be applied to the shaped plasticized superporous hydrogel material using a long, thin rod (e.g., 3-15 mm (preferably 6-10 mm) outer diameter) with its longitudinal axis oriented parallel to the central longitudinal axis of the hydrogel sample (i.e., parallel to one or more through-holes, if present) to create a linear depression or compression line on the side of the outer surface of the plasticized superporous hydrogel sample. The cylindrical sample can then be folded along this compression line to form a "quasi-cylinder," which can be crushed using three-way compression. Such three-way compression (involving primarily opposing biaxial forces with a small component of force in the third axis) can be performed, for example, by inserting the folded quasi-cylindrical sample of plasticized superporous hydrogel into a hollow, tapered tube and then pushing it along the inside of the tube to shape it, further compressing it, and reducing its diameter to a desired size (e.g., capsule diameter). The sample / capsule is preferably allowed to stand for 2-10 minutes (preferably 4-6 minutes) to completely set its shape, and then extruded from the open end of a tapered tube (preferably with an inner diameter of 26 mm). Alternatively, the folded sample can be forced into a cylindrical tube (e.g., with an inner diameter of 8-13 mm, preferably 9-10 mm) with two opposing open ends.Two push rods, each with a concave end, can be inserted into each of the two open ends of the cylindrical tube, and the concave ends are used to simultaneously squeeze the folded sample on opposite sides, thereby forming a compressed superporous hydrogel-containing capsule in the form of a lozenge with a rounded, domed end. It is also possible to directly mold (squeeze) the plasticized superporous hydrogel material into a capsule mold.

[0038] The folding step is most preferably performed on samples containing one or more through-holes, as these exhibit a particularly high diameter swelling ratio.

[0039] As mentioned above, the preparation of superporous hydrogel materials involves washing the initial hydrogel with an acidic solution followed by optional treatment with a monovalent salt solution, which may not require the formation of one or more through-holes, and therefore means that the sample of superporous hydrogel material does not need to be folded along a compression line as described above. Ideally, the plasticized superporous hydrogel sample can be simply three-way compressed, for example, by directly forcing it into a capsule mold or gelatin capsule shell or one of the tapered or cylindrical tubes described above.

[0040] Because materials are more easily deformed by external forces at temperatures above their glass transition temperature (Tg), the compressive force is preferably applied at an elevated temperature. Following application of the compressive force, the elevated temperature can be reduced, for example, to ambient temperature, as described above, to "set" the shape of the compressed plasticized superporous hydrogel. Furthermore, after mechanical processing, it is preferable to remove residual moisture in the compressed plasticized superporous hydrogel capsules, and therefore, it is preferable to further dry the product (e.g., in a desiccator or by re-lyophilization) to ensure long-term storage stability.

[0041] The compositions are ideally suited to providing product formulations comprising the plasticized superporous hydrogel material prepared by the methods of the present invention, optionally in a compressed form, optionally together with one or more slowly swelling non-superporous hydrogels. Preferably, the product formulations are suitable for use, for example, as appetite suppressants for controlling weight gain and preventing obesity, or for delivering pharmaceutical and / or nutritional supplements to the human or animal body.

[0042] The size of the product formulation (such as a capsule, tablet, or lozenge) is preferably a standard 000 capsule or other form of capsule, and insertion of the improved superporous hydrogel prepared by the method of the present invention is preferably achieved as described above.

[0043] In many applications, it is important that each plasticized superporous hydrogel material-containing capsule be able to swell to a size larger than the diameter of the patient's (human or animal) pylorus to ensure its retention in the stomach.

[0044] Although the product formulation of the present invention is designed not to block the esophagus or lower gastrointestinal tract, unforeseen accidents can occur. It is also desirable to be able to easily terminate the appetite suppressant formulation without the need for surgical, endoscopic, or other unpleasant medical intervention. The present invention addresses these issues by using a trigger or emergency exit mechanism to decompose the product formulation into a form that can be easily excreted by the patient. The "decomposition trigger" can have various forms, as long as it is effective and efficient in the decomposition process and safe for use by the patient. Preferred decomposition triggers include electromagnetic waves (e.g., light, heat), mechanical waves (e.g., ultrasound), or chemicals.

[0045] Depending on the nature of the hydrogel, the degradation trigger can be, but is not limited to, one of the following: (1) A solution containing specific chemicals that attack cross-linking groups. (2) Alkaline solutions reduce the mechanical strength of pH-sensitive hydrogels (3) a high-intensity focused ultrasound (HIFU) device targeting the hydrogel-containing composition; (4) Heat, light, or electrical signals delivered to the occlusion point by an endoscope or another capsule-like device, which trigger a response in the temperature-, light-, or electricity-sensitive hydrogel.

[0046] For example, the hydrogels of the present invention can be designed with reversible crosslinks that can be attacked by specific chemicals. While the reversible crosslinks are stable in the gastric environment, the chemical trigger is preferably one that is not normally consumed in daily life or that is present in food but in amounts too low to cause immediate degradation of the hydrogel. The amount and concentration should be strictly controlled within the acceptable ranges that can be found in regulations imposed by established authorities. Potential reversible crosslinks and their antidotes can include one or more of the following in Table 1:

[0047] [Table 1]

[0048] The improved compressively plasticized superporous hydrogel materials prepared by the methods of the present invention can be used in the treatment and / or prevention of one or more medical conditions, including, but not limited to, obesity and diabetes. Highly preferably, such hydrogels can be used as appetite suppressants.

[0049] In a further aspect, the present invention provides a dosing regimen for administration to a patient suffering from one or more medical conditions, e.g., selected from obesity and diabetes, comprising orally administering to the patient a first dose of an orally acceptable formulation comprising a high volume swelling hydrogel of the present invention in an amount or number of samples that swell upon ingestion to fill up to 80%, preferably up to 60%, and more preferably up to 50% of the patient's stomach volume.

[0050] In a preferred dosing regimen for treating obese or diabetic patients, an initial large first dose of preferably more than three, preferably at least five, and more preferably at least 20 orally acceptable tablets or capsules (any other suitable product formulation can also be used, preferably 000 size capsules) containing one or more high volume swellable hydrogels of the present invention is administered to the patient. This is then optionally followed by a second dose, and optionally further doses, preferably containing up to five orally acceptable tablets or capsules (or any other suitable product formulation) preferably containing one or more high volume swellable hydrogels (which may be the same or different from those incorporated in the initial large dose), at time intervals of at least about 12 hours, preferably at least about 24 hours, and most preferably longer, e.g., about 48 hours. Preferably, the high volume swellable hydrogel-containing product formulation is retained in the patient's stomach for several days (1-7 days), more preferably several weeks (1-30 weeks) or even longer. The optional second and subsequent doses may be the same as or different from one another.

[0051] Ideally, the above method also includes the patient ingesting about 200 ml of water (preferably lukewarm, more preferably about 37°C) before and / or during and / or after the patient ingests at least one of the first, second, or further subsequent doses.

[0052] Yet another separate invention provides a similar method for producing a body of plasticized superporous hydrogel material as described above, which includes a perforation step and an optional monovalent metal salt treatment step, but does not include an acid treatment step. The perforation treatment step has been found to be particularly useful because materials treated with non-acidic solutions generally have lower yields than their acid-treated counterparts, and the use of perforations allows the final plasticized superporous hydrogel material, molded or unmolded, to be folded / rolled into the desired shape for insertion into a 000-dose capsule. With the exception of the lack of acid treatment, all other steps, features, and advantages described above apply to this separate invention. [Brief explanation of the drawings]

[0053] The invention will now be described with reference to the representations in the following drawings. [Figure 1A] FIG. 1 shows a cross-sectional view of a mold containing an initial hydrogel material prior to sealing. [Figure 1B] 1B shows the same cross section of the same mold shown in FIG. 1A after sealing. [Figure 2A] FIG. 1 shows an end view of the circular end face of a cylindrical sample of plasticized superporous hydrogel with through-holes drilled along its central longitudinal axis, and of a cylindrical compression rod prior to being used to compress the hydrogel sample. [Figure 2B] 2B shows a cylindrical compression rod used to compress the cylindrical sample of plasticized superporous hydrogel shown in FIG. 2A. [Figure 2C] The cylindrical sample of plasticized superporous hydrogel shown in Figure 2B is shown being folded in the direction of the arrow with compression creases formed on its surface by the cylindrical compression rod (removed). [Figure 2D] The cylindrical sample of plasticized superporous hydrogel shown in FIG. 2C is shown after being folded to reduce its diameter. [Figure 3] FIG. 1 shows a cross-sectional view of two folded cylindrical samples of plasticized superporous hydrogel inserted into a hollow tapered cylindrical mold and push rod. [Figure 4A] Figure 1 shows a cross-sectional view of a folded cylindrical sample of plasticized superporous hydrogel inserted into a hollow, open-ended cylindrical mold with two push rods, one push rod inserted into each of the two open ends of the mold. [Figure 4B] Figure 4A shows a cross-sectional view of a folded cylindrical sample of plasticized superporous hydrogel inserted into a hollow open-ended cylindrical mold, as shown in Figure 4A, with two push rods compressing the sample on both sides. [Figure 4C] A sample of compressed, folded plasticized superporous hydrogel is shown in Figure 4B after release from the hollow, open-ended cylindrical mold. [Figure 5] FIG. 1 shows a graph of volumetric swelling ratio versus time for compressed and folded plasticized superporous materials produced according to the present invention in Control Example 1 (#OG) and Example 2 (#NG) using either water or simulated gastric fluid as the swelling medium. [Figure 6] FIG. 1 shows a graph of swelling diameter profiles versus time for compressed and folded plasticized superporous materials produced according to Control Example 1 (#OG) and Inventive Example 2 (#NG) using either water or simulated gastric fluid as the swelling medium. [Figure 7] 1 shows a graph of true stress versus time for compressed and folded plasticized superporous material produced according to Control Example 1 (#OG) using either water or simulated gastric fluid as the swelling medium. [Figure 8] 1 shows a graph of engineering stress versus time for compressed and folded plasticized superporous material produced according to Control Example 1 (#OG) using either water or simulated gastric fluid as the swelling medium. [Figure 9] 1 shows a bar graph illustrating the strength of compressed and folded plasticized superporous material produced according to the present invention in Example 2 (#NG) at 4 days in simulated gastric fluid. DETAILED DESCRIPTION OF THE INVENTION

[0054] Specific examples The abbreviations used herein are defined as follows:

[0055] [Table 2]

[0056] Example 1: (Control) Example 1: (Control) Preparation of a plasticized superporous hydrogel material (PSH) having one or more through-pores formed therein to aid in folding of the PSH to reduce its size and facilitate preparation of an oral dosage formulation.

[0057] Synthesis and Polymerization: Weigh out 16.0 g (+ / - 0.1 g) of AAm and 99.0 to 132.0 mg (+ / - 1 mg) of BAC and mix them with 90 to 200 ml of DW. Meanwhile, weigh out 20.0 g (+ / - 0.5 g) of AAm in 6.0 g (+ / - 0.1 g) of AL and mix them with 160 to 290 ml of DW. These two solutions were mixed together with 433.0 to 751.0 mg (+ / - 1.0 mg) of APS, and the resulting solution was evenly distributed among eight smaller beakers (marked as Group A).

[0058] Into each of another eight beakers (labeled Group B), 150.0 mg (+ / - 1.0 mg) of CaSO4 powder, 6.2 ml of water, and 47-82 μl of TEMED were weighed.

[0059] The solution in one of the eight beakers from Group A was poured into the suspension in one of the eight beakers from Group B. The mixture (14) was then stirred for 10 to 50 seconds and poured into four to eight molds (10). Each mold consisted of a cylindrical polypropylene (PP) tube (12) with an inner diameter of 10 to 40 mm and matching conical rubber stoppers (16, 18) at the top and bottom with the same outer diameter. The rubber stoppers (16, 18) were placed in the mold (10) as shown in Figures 1A and 1B.

[0060] The same procedure was repeated for all eight sets of solutions in Group A and Group B, and all samples in the PP molds (10) were placed in an incubator (preheated to 60 °C) for 1 hour. The molds (10) were then transferred to a humid chamber and cured at room temperature for an additional 24 to 72 hours to complete the polymerization. The resulting gelled material (initial hydrogel material) was labeled as the as-prepared gel (APG).

[0061] Freezing and freeze-drying: The APG gel in each mold (both ends of which were sealed with rubber stoppers) was placed in a -20°C freezer for 8 to 24 hours, and then transferred to a freeze dryer to remove water from the frozen gel for 48 to 72 hours, yielding freeze-dried superporous gels (freeze-dried SPH).

[0062] Through-hole formation: One or more through-holes or channels, 4-10 mm in diameter, were drilled along the longitudinal axis of each cylindrical sample of freeze-dried SPH to form a perforated freeze-dried SPH. The chips were blown away, e.g., using a fan.

[0063] Plasticization: A lidded container was half-filled with water, and the lidded container containing a sample holder capable of floating in the water was placed in an incubator at 60°C for 24 hours. A sample of the perforated freeze-dried SPH was then placed in the sample holder and placed in the container for 30–60 minutes until it became malleable.

[0064] compression: The malleable (plasticized), perforated, freeze-dried SPH (20, 26) was carefully removed from the container and compressed along the holes (22, 25) from the side of the sample using a rod (24), folding along the compression lines (28) to form a folded, plasticized, perforated, freeze-dried SPH (30) as shown in FIG. 2D, which was then either squeezed through an open-ended tapered tube to reduce its size to that of an oral dosage capsule, as shown in FIG. 3, or squeezed into a cylindrical tube and compressed with push rods (38a and 38b), each with concave ends (40a, 40b), each inserted into the opposing open ends of the cylindrical tube (36), as shown in FIGS. 4A and 4B, or molded directly in a capsule mold.

[0065] Example 2: Preparation of superporous hydrogel material using the process of the present invention, in which an acidic solution is used to treat the precursor initial hydrogel material to form one or more through-holes in the body of the sample while in the superporous hydrogel (SH) stage, further aiding in processing the PSH material into a lozenge-shaped body.

[0066] The synthesis and polymerization steps used in Example 2 to form the initial hydrogel material were identical to those used in Example 1.

[0067] Treatment with acidic solutions: The rubber stoppers (16, 18) were removed from the mold (10) shown in Figure 1B, and DW was used to wet the interface between the APG and the PP tubing (12), allowing the APG to slide out of the tubing for the next washing process.

[0068] APGs were soaked in SGF (pH approximately 1.3) for 7–14 days, with routine procedures including rinsing the samples and containers with DW and refreshing the SGF. The volume of SGF used to soak the samples ranged from 15–50 ml per gel.

[0069] Freezing and freeze-drying: The swollen and acid-washed samples were then removed from the SGF, and each hydrogel was placed directly into a PP cylindrical tube with a diameter similar to that of the swollen gel. The swollen gel inside the mold was then placed in a -20°C freezer for 8 to 24 hours and then transferred to a freeze dryer to produce freeze-dried superporous hydrogels (freeze-dried SPH).

[0070] Through-hole formation: One or more through-holes or channels, 4-10 mm in diameter, were drilled along the longitudinal axis of each cylindrical sample of freeze-dried SPH to form a perforated freeze-dried SPH. The chips were blown away, e.g., using a fan.

[0071] Plasticization: A lidded container half-filled with water and containing a sample holder capable of floating in the water within the container was placed in a 60 °C incubator for 24 h to ensure a uniform temperature. The freeze-dried SPH with the hole was then placed in the sample holder and placed in the container for 5–20 min until it became malleable.

[0072] compression: The malleable (plasticized) freeze-dried SPH sample was carefully removed from the container and compressed along the holes (22) from the side of the sample (20) using a rod (24), as shown in Figures 2A and 2B, and folded along the compression lines (22) as shown in Figures 2C and 2D. The resulting folded sample of plasticized freeze-dried superporous hydrogel (30) was squeezed into a cylindrical tube (36) with an inner diameter of 9-10 mm, as shown in Figure 4A. Two studs (38a and 38b) (outer diameter 9-10 mm) with specially fabricated dome concave surfaces at one end (40a and 40b) were placed on either side of the sample (30) in the tube (36) and pressed toward the center to form a rounded-ended hydrogel capsule (42), which was then removed from the tube as a free capsule (lozenge dosage form body) (44), as shown in Figure 4C.

[0073] result: The degree of swelling can be measured in several different ways, for example:

[0074] 1) Record the change in size by placing the sample on a calibration grid (1 cm square) before and after swelling.

[0075] 2) The initial volume of the dried gel is first measured using the ethanol displacement method. The gel is placed in a graduated cylinder filled with pure ethanol and pressed down with a thin needle to soak the ethanol. The displacement of the liquid surface is calculated and used as the initial volume of the dried gel. To measure the amount of ethanol displaced, remove the gel from the ethanol, dry it (e.g., using a clean tissue), and place it in a fume hood for 1 hour to evaporate the residual ethanol before placing the gel sample in a swelling medium (e.g., water or SGF). Once swelling is complete, the swollen gel volume is determined using the same liquid displacement method as described above, but using a swelling medium instead of ethanol as the liquid. The difference between the volume of displaced ethanol and the volume of the displaced swelling liquid is used to determine the swelling volume ratio of the gel.

[0076] 3) The length and diameter of the hydrogel sample before and after swelling are measured using calipers.

[0077] Both Examples 1 and 2 produced compacted plasticized superporous hydrogel materials, however, the material produced in Example 2 (#NG) achieved faster swelling results, with maximum swelling size achieved in approximately 20 minutes (in SGF and water) compared to the hydrogel produced using Example 1 (#OG), which required over 60 minutes to achieve the same degree of swelling.

[0078] Summary of results:

[0079] [Table 3]

[0080] Example 3: Experiments investigating the effect of pH on the appearance and swelling performance of plasticized superporous hydrogel materials produced by the method of the present invention.

[0081] Using the synthesis and polymerization process used in Control Example 1, 13 separate samples of the initial hydrogel material were prepared and each was individually cast into a mold (10). Each molded sample was then treated in accordance with the present invention as follows.

[0082] Treatment with acidic solutions: The rubber stoppers (16, 18) were removed from each mold (10) shown in Figure 1B, and DW was used to wet the interface between the APG and the PP tubing (12), allowing the APG to slide out of the tubing for the next cleaning process. Each APG sample was immersed in its own acidic solution, each with a different pH, ranging from pH 1 to 12. Thirteen APG samples were immersed in SGF (pH of approximately 1.3) for 7 days. The volume of acidic solution used to immerse the samples ranged from 15 to 50 ml per gel.

[0083] Freezing and freeze-drying: The swollen, acid-washed samples were then drained from the final acid solution, and each acid-treated hydrogel sample was placed directly into a 30 mm diameter cylindrical tube mold, longer than the length of the gel and open at only one end. The swollen gel inside the mold was then placed in a -20°C freezer for 8 to 24 hours and then transferred to a freeze dryer to produce freeze-dried superporous hydrogels (freeze-dried SPH).

[0084] Plasticization: Each freeze-dried superporous hydrogel sample was plasticized using the following method: A 0.4 L lidded container with an inner surface containing a moisture-wicking material (e.g., small pieces of absorbent paper moistened with 1 ml of water each) was placed in the container. The container was heated to 60°C for 5 minutes. The freeze-dried SPH sample was then placed in the container (well away from the moisture-wicking material) and the container was placed back in a 60°C oven for 1–5 minutes (ideally 3 minutes) until the sample became malleable.

[0085] compression: Each malleable (plasticized) freeze-dried SPH sample was carefully removed from its container and compressed along the hole (22) from the side of the sample (20) using a rod (24) as shown in Figures 2A and 2B. The sample was then folded along the compression lines as shown in Figures 2C and 2D. The resulting folded plasticized freeze-dried superporous hydrogel sample (30) was then squeezed into a cylindrical tube (36) with an inner diameter of 9–10 mm as shown in Figure 4A. This was achieved using a crimping machine that applied uniform radial compression along the long axis of the sample. The degree of swelling was measured by recording the weight of each sample of SPH material before swelling in distilled water at 37 °C, recording the length and diameter of each swollen sample, and recording the % volume expansion over time.

[0086] Results As shown in Table 4 below, the SPH samples showed an increase in % swelling as the pH of the acidic treatment solution increased from 1 to 12, with the greatest increase recorded for the pristine hydrogel samples treated with acidic solutions of pH 1 to 3. While the pristine hydrogel samples treated with acidic solutions of pH 4-11 continued to increase in % swelling, the rate of this increase caused the SPH samples to reach a plateau, and when a treatment solution of pH 12 was used, the respective SPH samples collapsed.

[0087] [Table 4]

[0088] Other important observations made during this experiment include the following: i) As the pH of the acidic solution used to treat the initial hydrogel increases, the mechanical stability of the target SPH decreases. This is observed by the loss of structural integrity in the SPH samples; when an acidic treatment solution of pH 1-3 is used, the SPH samples have a defined cylindrical shape, but this shape becomes increasingly distorted as the pH increases to pH 11, eventually becoming amorphous when the treatment solution is pH 12. ii) As the pH of the acidic solution used as the immersion fluid increases, swelling increases, but the target SPH material becomes increasingly unusable. iii) The desired cloudy / translucent appearance of the SPH is only observed when the initial hydrogel from which each SPH sample is formed is treated with an acidic solution of pH 1-3. This cloudiness / translucency is understood to be caused by porosity in the hydrogel.

[0089] It was found that the time required to treat each sample under high humidity conditions varied significantly depending on the pH of the acidic solution. Conclusion: The pH of the acidic solution used to process the initial hydrogel material is particularly important to ensure good processability and must be below pH 3 to provide optimal conditions for the desired pore size and desired expansion ratio while maintaining structural integrity.

[0090] Example 4: Experiment to determine the effect of pH and potassium chloride treatment on swelling behavior. Using the synthesis and polymerization process used in Example 1, 20 separate samples of the initial hydrogel material were prepared and each was individually cast into a mold (10). The initial hydrogel material samples were then divided into four batches: one batch was treated with an acidic solution at pH 1, another with a pH 1.3 solution, another with a pH 2 solution, and the remaining batch was treated with a pH 7 solution. Five samples from each batch were then treated with an aqueous solution containing 0M to 1M potassium chloride salt. Following this, each sample was freeze-dried, plasticized, and compressed as described above in Example 3. The resulting molded SPH samples were immersed in distilled water at 37°C. The length (mm) and diameter (mm) of each swollen sample were recorded, as well as the % volumetric expansion over time.

[0091] The complete experiment was repeated four times, and each % volume gain value shown in Table 5 below is the average of the four results obtained for the corresponding sample from each repetition of the experiment. The results show that the potassium chloride concentration has little effect on the final swelling weight upon immersion for samples generated from initial hydrogel samples treated with acidic solutions at pH 1-2, but a much larger % weight gain is observed when the treatment solution is pH 7, as expected from Experiment 3 above. However, quite surprisingly, the % volume change after 60 minutes is affected by the potassium chloride concentration; specifically, the % volume expansion increases as the potassium chloride concentration increases from 0 M to approximately 0.134 M (10 g), and then the expansion decreases as the concentration reaches approximately 0.5 M.

[0092] Conclusion: The addition of KCl >0.134M is a particularly useful range.

[0093] [Table 5]

[0094] Example 5: Experiments to determine the effect of monovalent metal salt concentration on the processability of target SPH materials. A key characteristic of the required plasticized superporous hydrogel material is its ease of shaping (e.g., folding / rolling / compression) to enable insertion into a medication capsule shell within a reasonable time frame (preferably more than 1 minute but less than 60 minutes). There is a delicate balance between an SPH material with excellent processing properties and one that is too soft. This study surprisingly established that for a given degree of water vapor treatment (exposure to moisture: % humidity and duration) used to plasticize the SPH sample, the "processability" (ease of folding / rolling / compression) of the SPH sample increases as the KCl concentration increases, making the SPH material more "processable." However, too much KCl, typically above 0.15 M metal salt concentration, can make the target SPH too soft to be easily processed.

[0095] A useful consequence of this observation is that the addition of KCl helps to control and optimize the amount of moisture exposure (duration and / or humidity %) a sample of dry SPH material needs to soften it, and concentrations of KCl salt from >0 M to 0.15 M allow for reduced humidity / shortened moisture exposure time compared to no KCl salt.

[0096] Conclusion: Optimal moisture exposure is obtained when monovalent salt solutions >0M to 0.15M are used.

Claims

1. 1. A method for preparing a plasticized superporous hydrogel, comprising: a) forming an initial hydrogel material in the absence of any foaming agent or other foaming means, said initial hydrogel material comprising one or more selected from an interpenetrating network, a semi-interpenetrating network, and a simply crosslinked structure formed by providing a mixture comprising one or more hydrophilic polymers and / or copolymers and subjecting said mixture to polymerization and / or crosslinking conditions; b) recovering the resulting initial hydrogel material formed in step a) and treating it with an acidic solution comprising one or more acids and having a pH in the range of <1 to ≦3; c) treating the initial hydrogel material formed in step a) with a ≧0M to ≦0.5M solution comprising one or more monovalent metal salts either simultaneously with or after treating step b); d) drying the resulting wet embryonic hydrogel material using freeze-drying to produce a dry superporous hydrogel material; e) treating the resulting dry superporous hydrogel material to plasticize its structure; f) recovering the resulting plasticized superporous hydrogel material. A method comprising:

2. 10. The method of claim 1, wherein the resulting plasticized superporous hydrogel material is in the form of individually separated samples comprising a body having an interior structure and an exterior surface comprising plasticized superporous hydrogel material, each sample comprising one or more through holes forming a passageway within the interior structure of the body extending between a first opening in a first portion of the exterior surface of the hydrogel material body and a second opening in a second portion of the exterior surface of the hydrogel material body.

3. 3. The method of claim 1 or 2, wherein individual samples of the initial hydrogel material are prepared by filling a reaction mixture comprising one or more hydrophilic polymers and / or copolymers into a suitable mold and demolding the resulting individual samples of the initial hydrogel material prior to subjecting the mixture to polymerization and / or crosslinking conditions.

4. 4. The method of claim 3, wherein the individual samples of the initial hydrogel material are cubes, cuboids, ovals, pellets, beads, balls, cylinders, rods, or irregular shapes.

5. 5. The method of claim 1, wherein step e) comprises subjecting the superporous hydrogel to >50% humidity conditions.

6. 6. The method of any one of claims 1 to 5, wherein the one or more monovalent metal salts are water-soluble alkali metal salts.

7. 7. The method according to any one of claims 1 to 6, wherein the one or more acids are selected from inorganic and / or organic acids.

8. The method of any one of claims 1 to 7, wherein the acidic solution comprises one or more selected from gastric juice and artificial gastric juice.

9. 9. The method of any one of claims 1 to 8, further comprising applying a compressive force to the resulting plasticized superporous hydrogel material to reduce the volume of at least some of the pores therein.

10. 10. The method of any one of claims 1 to 9, comprising the further step of inserting the resulting plasticized superporous hydrogel material into a capsule dosage shell to produce a capsule dosage.

11. 11. The method of claim 10, wherein the resulting plasticized superporous hydrogel material is inserted into a capsule dosage shell using one or more techniques to reduce the overall size of the resulting hydrogel body selected from the application of pressure, folding, extrusion, application of two-way and / or three-way pressure prior to insertion into the capsule dosage shell.

12. 12. The method of claim 11, wherein the resulting plasticized superporous hydrogel material is extruded through a hollow tapered tube before being inserted into a capsule dosage form shell.

13. 13. The method of any one of claims 1 to 12, wherein the initial porous hydrogel material comprises one or more hydrophilic polymers derived at least in part from acrylamide monomers or monomers containing acrylamide moieties.

14. 14. Use of one or more plasticized superporous hydrogels prepared by the method of any one of claims 1 to 13 for preparing a formulation suitable for oral administration.

15. 15. The use of claim 14, further comprising one or more pharmaceutical and / or nutritional supplements.

16. 14. An oral dosage formulation comprising one or more plasticized superporous hydrogels prepared by the method of any one of claims 1 to 13, optionally together with one or more pharmaceutical and / or nutritional supplements.